The regulation of the serum cholesterol level in man with particular reference to dietary factors - Gordon, Hymie (Division of Human Nutrition, 2020)
Fifty years ago, Ignatowski (1908) produced atherosclerotic lesions in rabbits by feeding them with a diet containing meat, milk and eggs. Since then, interest in the diet as a possible atherogenic factor has waxed and waned, but has never been greater than at present. Much of the credit for the present surge of interest is due to the Professor Ancel Keys of the University of Minnesota, who since 1952 has produce considerable evidence relating the development of coronary heart disease and the diet. His epidemiology surveys and his dietary experiments led him to favor the hypothesis which he summarized in the following terms (Keys, 1952).